Passive wake flow control of vertical axis wind turbines in array configurations - Jun-Kai Duan; Zi-Kang Wang; Hai-Ping Tian; Rui-Xue Feng; Wen-Bo Yao; Guo-Zhen Ma (Engineering Applications of Computational Fluid Mechanics)
This study introduces a passive wake control strategy for vertical axis wind turbine (VAWT) arrays using arc-shaped deflectors. Unlike prior works focusing solely on layout or blade optimization, this research systematically explores the effects of deflector position, orientation, and spacing on wake interaction and power output through two-dimensional CFD simulations. Results show that deflectors can redirect wakes and form high-speed flow channels, significantly enhancing downstream turbine performance. Under optimal conditions, the total power output increases by 112.27% compared to arrays without deflectors. The benefits are consistent across various tip speed ratios, especially at higher values. However, the analysis is limited to a four-turbine, 2D array, neglecting 3D effects and layout variations. These simplifications constrain the generality of the results. Future work should extend to larger and three-dimensional arrays to capture more realistic wake dynamics. Moreover, the deflector concept offers potential for multifunctional design, such as integrating photovoltaic panels for hybrid wind-solar systems. This work provides new insights into passive flow control in VAWT arrays, contributing to more efficient and compact wind farm designs.